Treatment Engagement Among Children Exposed to Violence: A Systems Perspective - Pinkerton, Linzy M. (Journal of interpersonal violence, 2023)
Childhood exposure to violence is a major public health issue. Effective treatment can reduce the impact of violence exposure on child outcomes. However, disparities in treatment engagement can interfere with effective treatment. This study reviews data collected from 2,546 children referred to community-based mental health services from 2001 to 2015 after exposure to violence. Children were categorized into three groups: those who attended intake but never started treatment, referred to as the Nonengager group; those who started but discontinued treatment prior to meeting treatment goals, referred to as the Attriter group; and those who completed treatment as rated by the treating therapist, referred to as the Completer group. The three groups were analyzed for differences in behavioral and emotional problems, racial identity, child social support, household income, number of people living in the home, parent stress, parent social support, community violence exposure, and neighborhood-level child opportunity. Analyses demonstrated that the Completer group were more likely to: live in neighborhoods with higher levels of childhood opportunity, identify as White, have an annual household income of $40,000 or greater, have significantly fewer people living in the home, report lower levels of parental stress, report higher levels of parental social support, report higher levels of child social support, and have significantly lower scores of emotional and behavioral problems after treatment. Overall, our study supports the importance of considering multiple ecological levels when targeting treatment engagement for children after exposure to violence. Results indicate that children from more advantaged environments are more likely to complete treatment, which leads to better outcomes. This can exacerbate existing disparities. Findings highlight the need for systems change and advocacy for children in less advantaged environments and meeting families in their specific context, to combat treatment disparities.